2013
DOI: 10.1051/fruits/2013094
|View full text |Cite
|
Sign up to set email alerts
|

Mango-based orchards in Senegal: diversity of design and management patterns

Abstract: -Introduction. Mango-based orchards in Senegal occur in a large diversity of cropping systems, but few typologies of these systems exist and none are associated with their comprehensive and quantitative analysis. In this study we defined and characterized the typology of these systems based on a quantitative assessment of their planting design, management, vegetative state, hedgerow structure and infestation by a major pest of mango, the Bactrocera invadens fly. Materials and methods. Multivariate analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 30 publications
0
22
0
9
Order By: Relevance
“…The previous study by Grechi et al (2013) in the same agroecosystems showed a close relation between the locality and the orchard type. A causal link between the climatic parameters of localities and orchard type is unlikely because the design and management of orchards in the same study zone were mainly based on historical, sociological and economic choices rather than on environmental grounds (Vannière et al, 2004).…”
Section: Ant Community Structure Depending On the Locality And The Ormentioning
confidence: 67%
See 4 more Smart Citations
“…The previous study by Grechi et al (2013) in the same agroecosystems showed a close relation between the locality and the orchard type. A causal link between the climatic parameters of localities and orchard type is unlikely because the design and management of orchards in the same study zone were mainly based on historical, sociological and economic choices rather than on environmental grounds (Vannière et al, 2004).…”
Section: Ant Community Structure Depending On the Locality And The Ormentioning
confidence: 67%
“…Type (4) orchards, which displayed higher intensification levels with a less diversified set of trees (Grechi et al, 2013), had the lowest ant diversity and richness. On the other hand, type (3) orchards, with the greatest tree richness, planting densities and variation in local planting density (Grechi et al, 2013), had the greatest ant diversity and richness. These results confirm previous studies showing the frequent increase in ant diversity and richness observed in heterogeneous landscapes Fig.…”
Section: Ant Diversity Ant Richness and Relations With Orchard Typementioning
confidence: 99%
See 3 more Smart Citations